The big snow - Hader, Berta; Hader, Elmer, 1889-1973. (New York : Aladdin Books ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1993)
Despite their elaborate preparations for the winter, the animals and birds are delighted by a surprise banquet after a big snow.
Art techniques used: Full color watercolor paintings.
CALDECOTT AWARD
Keywords: Animals -- Juvenile fiction; Caldecott Medal; Winter -- Juvenile fiction; Animals -- Fiction; Winter -- Fiction